"For research use only": A comprehensive analysis of SARMs and related IPEDs purchased on local Australian websites between 2017 and 2018. Issue 3 (October 2021) - Chakrabarty, Rima; Grainger, Janelle; Goebel, Catrin; Brooker, Lance; George, Adrian
Abstract: Introduction: The range of image and performance enhancing drugs (IPEDs) available is expanding beyond anabolic-androgenic steroids to alternatives such as selective androgen receptor modulators (SARMs). Many have yet to complete clinical trials, so their toxicity and drug-drug interactions are unknown. Yet, they are easily accessible online and are marketed for synergistic use in cycles. This poly-drug use has implications in anti-doping and public health. Comprehensive studies on these products are lacking, particularly research focused on the Australian market, leading to a deficiency in understanding of the nature and use of these alternative IPEDs. Method: Australian online retailers were surveyed, and 107 oral liquid products purporting to contain IPEDs were purchased between 2017 and 2018. A further 4 were obtained from a drug seizure. The product websites, packaging, contamination, and main active pharmaceutical ingredients were used to assess the product quality, to gain a holistic understanding of the products. A month-long stability test was conducted to identify other potential risks associated with the use of these products in Australia. Results: Most online retailer websites were still live in 2019, notwithstanding changes in the Poisons Standard regarding popular IPEDs. Just over half the products were still available on the same website. Most homepages featured fitspo imagery, notably including women. Product-specific pages often featured a "for research use only" warning and presented usage details informally. The packaging also featured the "for research use only" warning, while lacking many requirements of true therapeutic goods. Qualitative chemical analysis revealed that while 94 of the 111 products correctly identified the main active pharmaceutical ingredient on the label, 90 were contaminated with other IPEDs. Validated quantitative chemical methods assessed dosage strength and homogeneity to reveal that only 34 of the 111 were considered of good quality. Uniting the chemical analysis data revealed that the only high quality IPED was one of the seized products. Additionally, the stability test revealed that these IPEDs are generally stable across the different conditions tested, approximating Australian weather extremes. Conclusion: This research has strengthened concerns over the quality of IPED products sold on the Australian market and indicates there is no relationship between IPED product presentation and its chemical quality. The high proportion of contaminated IPED products may lead to poly-drug positives in doping control and possible adverse health effects due to drug-drug interactions. Education on IPEDs must expand to include these other classes to protect the community.